Efficiency of the Sanction Determination Process for Members of the Republic of Indonesia Police Who Have Violated the Code of Ethics - Iwansyah, Iwansyah; Santiago, Faisal (Cognitionis Civitatis et Politicae, 2025)
Enforcement of the code of ethics in the Indonesian National Police (Polri) is an important aspect of maintaining the professionalism and integrity of the institution. This study aims to analyze the efficiency of the process of enforcing the code of ethics in the Polri with a focus on the speed of case resolution, accuracy and consistency of sanctions, and its impact on the discipline and professionalism of Polri members. This study also identifies steps that can improve efficiency, such as simplifying administrative procedures, strengthening the capacity of the Profession and Security Unit (Propam), and utilizing information technology. The results of the study indicate that efficiency in enforcing the code of ethics can be achieved by accelerating the administrative process, improving the quality of human resources in Propam, and integrating information systems that facilitate coordination between units. This study provides recommendations for strengthening internal procedures and increasing transparency and accountability in the law enforcement process in the Polri